Economic Evaluation of Fiscal Regime on EOR Implementation in Indonesia: A Case Study of Low Salinity Water Injection on Field X - Adityawarman Adityawarman; Faridh Afdhal Aziz; Prasandi Abdul Aziz; Purnomo Yusgiantoro; Steven Chandra (Universitas Islam Riau (UIR) Press, 2020)
There are currently two fiscal regimes designated for resource allocation in Indonesia’s upstream oil and gas industry, the Production Sharing Contract Cost Recovery (PSC) and Gross Split. The Gross Split in the form of additional percentage split is designed to encourage contractors to implement Enhanced Oil Recovery (EOR) in mature fields. Low Salinity Water Injection (LSWI) is an emerging EOR technique in which the salinity of the injected water is controlled. It has been proven to be relatively cheaper and has simpler implementations than other EOR options in several countries. This study evaluates the LSWI project’s economy using PSC and Gross Split and then to be compared to conventional waterflooding (WF) project’s economy. There are four cases on Field X that are simulated using a commercial simulator for 5 years. The cases are evaluated under PSC and Gross Split to calculate the project’s economy. The economic indicators that will be evaluated are the Net Present Value (NPV) and sensitivity analysis is also conducted to observe the change of NPV. The parameters for sensitivity analysis are Capital Expenditure (CAPEX), Operating Expenditure (OPEX), Oil Production, and Oil Price. It is found that LSWI implementation using Gross Split is more profitable than PSC. The parameters that affects NPV the most in all PSC cases are the oil production and oil price. On the other hand, in Gross Split cases, the oil production is the parameter that affects NPV the most, followed by oil price. The novelty of this study is in the comparison of project’s economy between WF and LSWI using two different fiscal regimes to see whether Gross Split is more profitable than PSC on EOR implementation, specifically the LSWI at Field X.